PENGARUH PENGGUNAAN PANTOEA AGGLOMERANS DAN ETEROBAKTER CLOACAE PADA PERENDAMAN BENIH TERHADAP PERTUMBUHAN TANAMAN KEDELAI (Glycine Max L. Merril) - Dewa Gede Suarjaya; I Gede Rian Pramarta; Erlina Kertikasari; Devita Ari Safitri (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Soybean ( Glycine max L. Merril) is a strategic commodity in Indonesia. This is affected by the use of soybeans not only to fullfil food needs, but also to support agro-industry. The purpose of this research is to increase growth and productivity soybean plant through induction rhizobacteria P. agglomerans and E. cloacae as well as the combination . The treatment was applied by soaking the seeds in bacterial suspension and watered again with the bacterial suspension at a dose of 10 ml/polybag. Observed variables are: maximum plant height, maximum number of branches, maximum number of leaves, growth analysis, number of root nodules on soybean roots, fresh root weight, oven-dried root weight, weight of oven-dried plant canopy and total leaf chlorophyll content. Application P. agglomerans and E. cloacae increase yields of soybeans. Treatment of P. agglomerans and E. cloacae had a very significant effect on most of the observed growth parameters, except for the variable oven-dried weight of plant canopy.